Correlating the role of nanofillers with active layer properties and performance of thin-film nanocomposite membranes - Perry, Lamar A.; Chew, Nick Guan Pin; Grzebyk, Kasia; Cay-Durgun, Pinar; Lind, Mary Laura; Sitaula, Paban; Soukri, Mustapha; Coronell, Orlando (Desalination, 2023)
Thin-film nanocomposite (TFN) membranes are emerging water-purification membranes that could provide enhanced water permeance with similar solute removal over traditional thin-film composite (TFC) membranes. However, the effects of nanofiller incorporation on active layer physico-chemical properties have not been comprehensively studied. Accordingly, we aimed to understand the correlation between nanofillers, active layer physico-chemical properties, and membrane performance by investigating whether observed performance differences between TFN and control TFC membranes correlated with observed differences in physico-chemical properties. The effects of nanofiller loading, surface area, and size on membrane performance, along with active layer physico-chemical properties, were characterized in TFN membranes incorporated with Linde Type A (LTA) zeolite and zeolitic imidazole framework-8 (ZIF-8). Results show that nanofiller incorporation up to ~0.15 wt% resulted in higher water permeance and unchanged salt rejection, above which salt rejection decreased 0.9–25.6 % and 26.1–48.3 % for LTA-TFN and ZIF-8-TFN membranes, respectively. Observed changes in active layer physico-chemical properties were generally unsubstantial and did not explain observed changes in TFN membrane performance. Therefore, increased water permeance in TFN membranes could be due to preferential water transport through porous structures of nanofillers or along polymer-nanofiller interfaces. These findings offer new insights into the development of high-performance TFN membranes for water/ion separations. [Display omitted] •Nanofillers were embedded into TFN active layers at <1 at.%.•Physico-chemical characterizations of active layers were representative of polymer.•Salt rejection above nanofiller loading threshold of ~0.15 wt% was markedly lower.•Changes in membrane physico-chemical properties and performance were not correlated.•Flow through nanofiller/along nanofiller-polymer interface likely boosts permeance.